Morphological and physiological changes in papaya seedlings irrigated with saline water and application of humic substances - Dias, Thiago Jardelino; da Silva Leal, Marcia Paloma; do Nascimento, Everaldo Silva; Veras, Mario Leno Martins; Silva, Toshik Iarley da; Lopes, Adriano Salviano (Comunicata Scientiae, 2020)
In the northeast semiarid region water with high salt content is very common, which may negatively affect crops growth and development. Thus using possible salt stress attenuators is extremely important because it allows the use of saline waters for agricultural purposes. Among the possible attenuators of salt stress, humic substances stand out. This work was driven in order to evaluate the effect of the application of humic substances as a possible attenuator of salt stress from papaya seedlings irrigation. The experiment was conducted under entirely randomized design with five replications in a 4 x 4 factorial, regarding the four doses of humic substances (5, 10, 15 and 20g), and the electrical conductivity of the irrigation water (ECw 1.5; 3.0; 4.5 and 6 dS m-1). When it irrigates the papaya seedlings with water of 6.0 dS m-1 is recommended dose of 20 g of humic substances, which provided growth. Irrigation of papaya seedlings with high salinity (3.0 and 4.5 dS m-1) allied with application of 20 g of humic substances provide increased CO2 concentration, transpiration rate, instantaneous water use efficiency, carboxylation efficiency and chlorophyll b content, however, stomatal conductance, net photosynthesis and chlorophyll a content are reduced with increase of the ECw.